KERJA SAMA UN WOMEN DENGAN GOJEK DALAM MENDORONG TERCAPAINYA AGENDA SUSTAINABLE DEVELOPMENT GOALS 5: GENDER EQUALITY DI INDONESIA PERIODE 2020-2022 - Indah Jullanar (2023)
The issue of gender inequality and discrimination against women presents limitations for women to obtain equal rights and equal opportunities in various fields. The Sustainable Development Goals exist as a form of international agreement in their commitment to eradicate poverty which is projected to reach 2030. Gender equality also plays a role in becoming a goal that stands alone in the SDGs, namely goal 5 with the aim of achieving global gender equality. In this case, cooperation can be an alternative to be able to eliminate the gender gap and achieve the SDG 5 agenda. UN Women itself is the UN entity responsible for supporting the achievement of SDG-5. Meanwhile, Gojek as a platform-based technology company is active in campaigning for equal rights for women in the employment sector and women's economic empowerment. This study aims to analyze the collaboration between UN Women and Gojek which was agreed in July 2020 in encouraging the achievement of the Sustainable Development Goals 5 agenda: Gender Equality in Indonesia. The theory used is gender equality in the perspective of feminism, feminist institutionalism theory, and sustainable development. The research method used is a qualitative descriptive research method with a case study approach. Data collection was taken from primary and secondary sources through internet based research and the data analysis techniques used in this study were data reduction, data display, and conclusion drawing. The results of the research show that the form of cooperation carried out by UN Women and Gojek includes implementing training programs for Gojek driver-partners to be more aware of violence and sexual harassment of women in public spaces as well as training for women's economic empowerment. The research results also show that the collaboration between UN Women and Gojek is one of the parties participating in helping achieve the SDG 5 agenda. This is also evidenced by data from the WEF Report on the 2022 Global Gender Gap, where the gender equality index in Indonesia has increased from last year.